Modeling In Early Childhood Education: A Contribution to The Integral Development of the Child (Global Journal of Human-Social Science, 2023)
This writing deals with Modeling in the conception of Mathematics Education and has as its guiding question What elements of the Modeling tasks make it possible to contribute to the development of children in Early Childhood Education The objective is to explain the principles and constituent stages of the Modeling tasks that contribute to the child s development based on the analysis of 3 three dissertations supervised by Burak or authors who follow his assumptions Initially Higginson s conception and Mathematics Education 1980 and the conception of Modeling in Mathematics Education proposed by Burak 1992 are clarified This is qualitative bibliographic research As a result of the analyzes and descriptions of the dissertations it can be pointed out that the fact of making children the protagonist of their learning is a differential allows the child to act in an active complex way analyzing synthesizing information formulating hypotheses to explain the problem raised in addition to significantly favoring the development of fine and gross or broad motor coordination in expanding vocabulary in oral language in the form of expression of children and notably in self-confidence Modeling in the conception of Mathematics Education has a strong potential to constitute a new rationality in the teaching process in the scope of Early Childhood Education
Keywords: pedagogical practice; children; development; autonomy